2017
DOI: 10.1016/j.drugalcdep.2017.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of e-liquid flavors on nicotine intake and pharmacology of e-cigarettes

Abstract: Objectives To describe the effect of e-liquid flavors on nicotine intake and pharmacology of e-cigarettes. Methods 11 males and 3 females participated in a 3-day inpatient crossover study with strawberry, tobacco, and their usual flavor e-liquid. Nicotine levels were nominally 18 mg/ml in the strawberry (pH 8.29) and tobacco (pH 9.10) e-liquids and ranged between 3–18 mg/ml in the usual brands (mean pH 6.80). Each day consisted of a 15-puff session followed by 4 hours of abstinence, then 90 minutes of ad lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 34 publications
3
63
1
1
Order By: Relevance
“…We observed an increase in reports of the use of fruit flavoured e-liquids (35% to 51%) and a decrease in tobacco flavoured e-liquids (18% to 9%); a change which is consistent with national trends in e-cigarette flavours (ASH, 2017). Recent studies suggest that device type, PG/VG ratio , and flavours play a role in nicotine delivery (Farsalinos et al 2014;Kosmider at al 2018, St Helen et al 2017Spindle et al 2018) . Thus, changes to flavourings and device types including the subsequent increase in device power, may also contribute to more effective nicotine delivery helping to offset the effect of reducing nicotine concentration in the e-liquid.…”
Section: Resultsmentioning
confidence: 99%
“…We observed an increase in reports of the use of fruit flavoured e-liquids (35% to 51%) and a decrease in tobacco flavoured e-liquids (18% to 9%); a change which is consistent with national trends in e-cigarette flavours (ASH, 2017). Recent studies suggest that device type, PG/VG ratio , and flavours play a role in nicotine delivery (Farsalinos et al 2014;Kosmider at al 2018, St Helen et al 2017Spindle et al 2018) . Thus, changes to flavourings and device types including the subsequent increase in device power, may also contribute to more effective nicotine delivery helping to offset the effect of reducing nicotine concentration in the e-liquid.…”
Section: Resultsmentioning
confidence: 99%
“…Nicotine exposure studies typically incorporate single‐use sessions with fixed puffing bouts or short‐term ad‐libitum procedures. Plasma nicotine concentrations are typically higher from ad‐libitum use compared to fixed puffing , perhaps because ad‐libitum procedures allow e‐cigarette users to self‐administer aerosols to achieve desired nicotine levels. However, ad‐libitum periods used in pharmacokinetic studies are typically brief (5–115 minutes) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand the adverse events (AEs) associated with e‐cigarette use, it is useful to begin with the various chemicals found in these solutions as well as in the heated vapours which can be formed from chemical reactions resulting from the heating process . The solutions used to prepare the nicotine for vapourizing typically use a variety of solvents including propylene glycol, ethylene glycol, glycerol and polyethylene glycol with various concentrations of nicotine (see section ) and over 7000 flavouring agents that may add potentially toxic substances and possibly affect the pharmacokinetics of nicotine . Chemical analysis studies have identified many types of substances present in the vapours that can be categorized into four distinct chemical entities: carbonyl compounds, volatile organic compounds (VOCs), tobacco‐specific nitrosamines (TSNAs) and metals.…”
Section: Commentarymentioning
confidence: 99%